2017
DOI: 10.1590/s0100-736x2017000600003
|View full text |Cite
|
Sign up to set email alerts
|

Nasal swab real-time PCR is not suitable for in vivo diagnosis of bovine tuberculosis

Abstract: RESUMO.-[A PCR em tempo real de swab nasal não é adequada para o diagnóstico in vivo de tuberculose bovina.] A tuberculose bovina (bTB) é uma zoonose que causa perdas econômicas e riscos à saúde pública em muitos países. O diagnóstico da doença em animais vivos é realizado pelo teste intradérmico da tuberculina, que é baseado em reações de hipersensibilidade tardia. Como a tuberculose tem resposta imunológica complexa, este teste tem limitações em termos de sensibilidade e especificidade. Este estudo procurou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Zanini et al (1998) [27] and Zumarraga et al (2005) [30] evaluated PCR from nasal swab and milk in routine diagnosis of mycobacteria and reported its high sensitivity and specificity. In contrast, Mayer et al (2015) [14] reported that screening of nasal swab by PCR was not a suitable tool in the diagnosis of bovine tuberculosis by comparing with comparative cervical test. The prevalence of NTM by conventional isolation method was1.7%.…”
Section: Resultsmentioning
confidence: 98%
“…Zanini et al (1998) [27] and Zumarraga et al (2005) [30] evaluated PCR from nasal swab and milk in routine diagnosis of mycobacteria and reported its high sensitivity and specificity. In contrast, Mayer et al (2015) [14] reported that screening of nasal swab by PCR was not a suitable tool in the diagnosis of bovine tuberculosis by comparing with comparative cervical test. The prevalence of NTM by conventional isolation method was1.7%.…”
Section: Resultsmentioning
confidence: 98%
“…The major limitation of mycobacterial culture is being confined to PM lesion samples, some studies suggest the use of nasal swabs as an alternative method [75]. However, Mayer et al stated that RT-PCR from nasal swabs is not suitable for in vivo diagnosis of bTB [100] Near the fibrous capsule, the inflammatory cell population consisted of macrophages, lymphocytes, and scattered neutrophils. Stage IV granulomas exhibited mostly necrosis and mineralization.…”
Section: Mycobacterial Culturementioning
confidence: 99%
“…The major limitation of mycobacterial culture is being confined to PM lesion samples, some studies suggest the use of nasal swabs as an alternative method [ 75 ]. However, Mayer et al stated that RT-PCR from nasal swabs is not suitable for in vivo diagnosis of bTB [ 100 ].…”
Section: Diagnosis Of Btbmentioning
confidence: 99%